2021
DOI: 10.3390/ijerph18073810
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Lockdown and the Behavior Change on Physical Exercise, Pain and Psychological Well-Being: An International Multicentric Study

Abstract: Objective: To evaluate the impact of the COVID-19 pandemic and the following lockdown on physical exercise (PEx) practice, pain, and psychological well-being. Methods: A cross-sectional multicentric study was performed using a nonrandom convenience sampling from the general population (≥18 years-old) of 6 countries (Brazil, Italy, France, Portugal, Germany, and Spain) adopting social isolation (SI). The validated self-administered online survey (PEF-COVID19) was used. The tests T-test and Chi-square with Bonfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 61 publications
3
44
0
1
Order By: Relevance
“…The decrease in physical activity during the COVID-19 pandemic demonstrated in the current study was in line with our first hypothesis (H1) and agreed with previous investigations [1,4,9,32,[36][37][38][39][40][41][42]. The systematic review by Stockwell, et al, (2021), utilized 45 articles that assessed physical activity during COVID-19 in healthy adults, to conclude that all the studies reported total physical activity to decrease during COVID-19 [37].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The decrease in physical activity during the COVID-19 pandemic demonstrated in the current study was in line with our first hypothesis (H1) and agreed with previous investigations [1,4,9,32,[36][37][38][39][40][41][42]. The systematic review by Stockwell, et al, (2021), utilized 45 articles that assessed physical activity during COVID-19 in healthy adults, to conclude that all the studies reported total physical activity to decrease during COVID-19 [37].…”
Section: Discussionsupporting
confidence: 92%
“…Being in a lockdown environment (e.g., mandate to reduce time outside of home to slow down the spread of the infection) due to a lockdown may alter the activities in which individuals participate each day due to rapid changes in work and social environments, which may have a large impact on behavior and mood [8,9]. Research on the impact of COVID-19 lockdown and quarantine on mood found this resulted in negative psychological effects [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…These may be important contributing factors, and changes have been reported internationally with regard to physical exercise practice, habits, pain, anxiety and stress with greater changes being observed in Italy ( 25 ). Eating habits were carefully evaluated in a German study showing mainly an increase in food amount, and specifically in the assumption of bread and confectionary, and changes in alcohol consumption were also reported.…”
Section: Nutrition Adiposity and Physical Activitymentioning
confidence: 99%
“…Over the course of several waves, the impact of COVID-19 and isolation have been studied in various studies. It would have been interesting to collect data on such psychological aspects of the disease, like Sonza et al in their multicentric study [22] .…”
Section: Discussionmentioning
confidence: 99%